Binder Jetting 3D Printing of Titanium Aluminides Based Materials: A Feasibility Study - Yadav, Pinku; Fu, Zongwen; Knorr, Moritz; Travitzky, Nahum (Advanced Engineering Materials, 2020)
This study offers the ability to fabricate nearly dense titanium aluminides-based structures using a hybrid method that encompasses binder jetting 3D printing (3DP) of Ti–6Al–4V followed by pressureless ex situ infiltration with Al. Microstructure characterization and phase analysis are performed by scanning electron microscopy equipped with energy dispersive spectroscopy and X-ray diffraction, respectively. The microstructure of the samples fabricated by means of pressureless ex situ infiltration at different temperatures and with various durations is studied and discussed. The nearly dense titanium aluminides-based composites shows a Young's modulus of ≈145 GPa, a compressive strength of ≈1.4 GPa and a bending strength of ≈483 MPa. To demonstrate technological capability of this hybrid approach, complex near-net-shaped objects are fabricated.
CRIS-Team Scopus Importer:2020-06-09
Keywords: 3D printing; metal-matrix-composites; titanium 6–4; titanium aluminides

Novel Hybrid Printing of Porous TiC/Ti6Al4V Composites - Yadav, Pinku; Bock, Thomas; Fu, Zongwen; Lorenz, Hannes; Gotman, Irena; Greil, Peter; Travitzky, Nahum (Advanced Engineering Materials, 2019)
Porous TiC/Ti6Al4V composite samples are fabricated by novel hybrid 3D-printing (3DP)/sintering method using a blend of Ti6Al4V and dextrin powders as a precursor material. TiC/Ti6Al4V samples are 3D-printed with two different layer thicknesses of 0.150 and 0.175 mm, and subsequently sintered at various sintering temperatures and dwell times. X-ray analysis of the fabricated composites shows the presence of Ti and TiC. The maximum Young's modulus of porous TiC/Ti6Al4V samples is found to be ≈51 GPa. An overall porosity of the sintered samples ranges from 12% to 35% with a pore size of 65–160 μm. The bending strength ranges from ≈80 to ≈285 MPa depending on the sintering parameters. The compressive strength and hardness of the obtained composites are also reported. Binder jetting 3DP process overcomes the problem of fabricating complex structures and has an edge over conventional techniques such as casting, machining, etc. Several complex-shaped models are fabricated to demonstrate the net-shape capability of this approach.
CRIS-Team Scopus Importer:2019-06-21
Keywords: 3-dimensional printing; biomaterial; metal-matrix-composite; Ti6Al4V; titanium carbide